PEMANFAATAN WEBSITE SEBAGAI MEDIA PROMOSI DAN PENJUALAN DI UKM NADIRA CATERING - Arimbi Kurniasari (Jurnal Ilmiah Teknik, 2023)
The role of MSMEs is very large for Indonesia's economic growth, with their number reaching 99% of all business units. The development of MSMEs in Indonesia is considered quite rapid when viewed from the large number of MSMEs, so it is not surprising that MSMEs are a pillar of economic growth in the country. However, when the Covid 19 pandemic hit all countries, including Indonesia, MSMEs were one of the types of businesses most affected by the pandemic. Sales have decreased so that it also has an impact on the MSME's income. Nadira Catering is one of the MSMEs engaged in the accommodation and provision of food and drink which is located in the South Tambun area, Bekasi district. With a sales method that still only sells on the spot and customers come to the location to order catering services. When the pandemic hit, Nadira Catering was also affected because the number of buyers who ordered their services was much reduced. It is hoped that this website will help Nadira Catering to promote its products to a wider area so that it can attract new potential buyers to transact with Nadira Catering. This website can also help catering management to record, organize and make reports related to sales at Nadira Catering. This website is made user friendly so that users can easily find product information or make product purchases.